(untitled) (Fiep Bulletin - online, 2015)
It was objectified to answer Hobie Cat 16 sailors technical doubts like mechanical efficiency of the hiking positions generally adopted. It participated a pair of subjects composed with one of the masculine gender and one of the feminine gender. A SVHS camcorder was used (30Hz); with about 10 seconds acquisition for each position and the two-dimensional analysis was performed in the Peak Motus system software. Seven positions for each athlete had been analyzed (called HC1, HC2 and HC3 in two rope lengths and HC4 for the arms extension above the head). The athletes had presented similar knee and hip angles in the proposal situations. A gradual Hiking Moment increase was noticed when occurred the segments extension. From the most comfortable position (HC1) to HC2 position the mechanical efficiency increase was observed when increase in the angles of knee and hip happened, and for the positions HC3 and HC4 only one variation in the hip angle was observed, that resulted approximately an increase of 7% in the gesture efficiency. In the use of the arms were compared positions HC3 and HC4, being found an increase of 5% and 8% for athlete 1 and 2, respectively. However athlete 2 presented an exaggerated increase in the hip angle, that resulted in hyperextension of the lumbar region and great discomfort, as told for the athlete. Athlete 1 also presented an increase in the efficiency, however without the hyperextension of the lumbar region, being explained for a possible greater musculature preparation of the anterior region of the body. Small differences or possible adjustments between the sailors in the analyzed positions had been identified. These differences or strategies used for the athletes identified and argued with the technician can make possible one better understanding about the trapeze use and search the best performance.